The role of lymphadenectomy in breast cancer and skin melanoma treatment - Herman, Krzysztof; Pogodziński, Marek; Marczyk, Elżbieta (Contemporary Oncology/Współczesna Onkologia, 2004)
Radical lymphadenectomy is considered part of the standard treatment of invasive breast cancer and melanoma with regional nodes involved. However, for node-negative patients this treatment has become controversial, especially since in more and more patients early neoplasms are operated on. Furthermore, lymphadenectomies, while not being the most extensive oncological surgeries, are related to relatively frequent early and late complications, mainly lymphoedemas. In recent years, more and more scientific centers have tried to find out which patients with occult metastases can benefit from radical lymph nodes dissection and which cannot. The sentinel node biopsy is a reliable and minimally invasive method for determining the status of the regional lymph nodes in clinical melanoma and breast cancer node-negative patients. Immunohistochemical pathologic analysis of lymph nodes allows micrometastases and isolated tumor cells to be detected. Still, their prognostic and predictive value remains unclear. It is also unclear if the ”sentinel node” procedure improves overall survival in breast cancer and cutaneous melanoma patients. Relying on their own experience and literature, the authors show current contradictory data concerning the role of radical lymphadenectomy in breast cancer and melanoma treatment.